Pengembangan dan Evaluasi Kepraktisan E-Modul Manajemen Koperasi Berbasis Studi Kasus untuk Mahasiswa Pendidikan Ekonomi - Tuti Supatminingsih; Andi Asti Handayani (MASALIQ, 2026)
Cooperative Management learning in higher education still faces challenges in connecting theoretical concepts with real problems encountered by cooperatives, while the availability of contextual digital learning resources aligned with the characteristics of Economic Education students remains limited. This study aims to develop and evaluate the practicality of a case-study-based Cooperative Management e-module for Economic Education students. This study used the Research and Development (R&D) method with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of two expert validators and five Economic Education students as users in a small-group trial. Data were collected through validation sheets, practicality questionnaires, and documentation, then analyzed descriptively and quantitatively using percentages. The results showed that the developed e-module obtained a material validity level of 92.00% and a media validity level of 93.00%, both in the very valid category. The practicality test results showed a percentage of 92.50% in the very practical category. This e-module was able to support contextual learning, increase student engagement, and help students analyze cooperative cases more systematically. The conclusion of this study affirms that the case-study-based Cooperative Management e-module is feasible for use as a digital learning resource in Cooperative Management learning. The implications of this study indicate that the development of technology- and case-study-based learning resources can serve as an innovative alternative to improve the quality of Economic Education learning in higher education.